Rituximab-induced Crohn's disease. (4th May 2017) - Varma, Poornima; Falconer, Julianne; Aga, Ahmad; Prince, H. Miles; Pianko, Stephen
Abstract: The use of rituximab has significantly improved outcomes in patients with haematological malignancies and autoimmune disease. There are reports of rituximab-associated ulcerative colitis; however, we report for the first time, two cases of rituximab-induced Crohn's disease in elderly patients treated for lymphoma. Both patients had evidence of inflammation, ulceration, and granulomas consistent with Crohn's disease, and responded well to immunosuppression. The association of rituximab and ileocolitis suggests a protective effect of CD20 + lymphocytes in the gut, and implicates their depletion to the development and exacerbation of inflammatory bowel disease.